La fille en boîte : naissance d’une perversion au Japon - Agnès Giard (Criminocorpus)
In 1972, Shibusawa Tatsuhiko (1928-1987), translator of Georges Bataille and Marquis de Sade, publishes an essay – “Introduction to collections of girls” (Shôjo korekushon josetsu) – expanding the idea according to which girls, being objects by definition, arouse in men the desire to make a collection of them, i.e. to own several specimens of girls and preserve them in boxes. « More the individuality of a woman is restricted within the limits of her sole existence, more she is deprived of words, more she becomes nothing but a fragment of object, more man’s libido burns with a pale and burning flame », writes Shibusawa. Thanks (?) to him, the topic of the « girl in a box », whose origins can paradoxically be traced back to the speech of a trailblazing feminist, enjoys a tremendous success in the mainstream erotic culture of post-war Japan.